Motivation and retention of episodic volunteers in Saudi nonprofits: a case study of the MiSK Foundation - Al Homsi, Mohammed Ousamah (2018)
Nonprofit organizations play an essential role in economies by supplementing or replacing public goods and services Weisbrod (1986). However, in light of the the increasing demand on their products, coupled with their limited available financial resources (Karn, 1983), and the labour intensity of the sector (Hodgkinson et al., 1996), nonprofits are facing an increasing pressure that may put their missions and operations in danger. Therefore, volunteers have been largely relied on to address these challenges given their capacity to become an essential source of workforce. Generally speaking, voluntary action has been growing in different parts of the world, and volunteers are being largely considered as a powerful social force, and an essential component to social development (Korten, 1990). Those individuals are mainly driven by a purpose to tackle social issues and nurture the wellbeing of marginalized groups in their communities, whose issues may insufficiently be addressed by official institutions. Guided by their moral obligation rather than financial incentives, volunteers have played a significant role in social integration as well as economic development in different countries (Cheung, 2006). However, the element of unpredictability in sourcing volunteers, and the risks that are associated with managing them, such as the risk of their absenteeism and turnover, will hinder nonprofits’ abilities to make decisions and plan for future projects that in turn depend to a large extent on volunteers (Brudney, 2012, p.57).